New interpretations of the genus Sinocyrtaspis Liu, 2000 (Orthoptera: Tettigoniidae: Meconematinae) from China - Wang, Tao; Xin, Yarui; Shi, Fuming (Zootaxa, 2020)
In this paper, one new species of the genus Sinocyrtaspis Liu, 2000, i.e. Sinocyrtaspis megalobia sp. nov. and the previously unknown male of Sinocyrtaspis huangshanensis Liu, 2000 are described from China. Meanwhile, Sinocyrtaspis brachycerca Chang, Bian & Shi, 2012 is downgraded to subspecies of Sinocyrtaspis huangshanensis Liu, 2000.